Whither development studies? Reflections on its relationship with social policy - James Copestake (University of Bath, Centre for Development Studies (CDS), 2014)
This paper contributes to an on-going conversation between development studies (DS) and social policy (SP) as academic fields, particularly in the UK. Drawing on Andrew Abbott's analysis of the social sciences as an evolving system of knowledge lineages (KLs) it reflects first on the status of DS, and then on its relationship with SP. Defining DS as a distinctive KL centred on critical analysis of diverse ideas and projects for advancing human wellbeing, I suggest that it has lost coherence and influence even as research into international development thrives. Indeed it is easy to envisage its gradual assimilation into other KLs, including SP. The two increasingly overlap in their analysis of the causes of relative poverty and injustice, and what can be done to address them, within countries and globally. Strengthening links between the two fields can be justified as a political project, even at the risk of some loss of plurality and plenitude across the social sciences.
Keywords: 330; Development studies; social policy; social sciences; poverty